COMPARISON OF 3 DIFFERENT TREATMENT METHODS FOR GENERALIZED DENTURE STOMATITIS - ÖZKAN, YASEMİN (MOSBY-YEAR BOOK INC, 1994)
This study compared the effects of fluconazole, fluconazole plus chlorhexidine, and placing new dentures for the treatment of generalized simple denture stomatitis. Subjects with clinical evidence of generalized simple denture stomatitis were investigated clinically and myocologically. These 45 patients were divided into three groups. The first group was given 50 mg of fluconazole in tablet form once a day for 2 weeks. The second groups were instructed to apply chlorhexidine solution to the inner surface of the denture twice a day in addition to the fluconazole treatment for 2 weeks. New dentures were made for the third group. Palatal swabs and smears were taken from each subject before, immediately after, and 2 weeks after treatment and these samples were examined myocologically. It was found that for generalized simple denture stomatitis, treatment with fluconazole in conjunction with chlorhexidine resulted in greater improvement of palatal inflammation and a decrease in candidal colonization than that with fluconazole alone or making new dentures without medication.
Keywords: ORAL CANDIDIASIS; FLUCONAZOLE; NYSTATIN; EFFICACY